2004
DOI: 10.1111/j.1439-0264.2004.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Villus Histological Alterations in Piglets fed Dietary Charcoal Powder Including Wood Vinegar Compound Liquid

Abstract: To investigate the effects of dietary charcoal powder including wood vinegar compound liquid (CWVC, 4 : 1) on intestinal villus histology, piglets were fed 0, 1, 3 and 5% dietary CWVC diets for 30 days. Feed intake and body weight gain were measured during the experimental period. At the end of the experiments, intestinal villus height, epithelial cell area and cell mitosis were examined using light microscopy (LM), and the duodenal villus tip surface was observed using scanning electron microscopy (SEM). Feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 31 publications
3
46
1
Order By: Relevance
“…These studies suggest that the present high light microscopic parameters and the protuberated cells are much more hypertrophied in CWVC than in PM groups. In our previous studies, such histological intestinal recovery from the atrophied intestinal histology in raw PM groups was observed after feedings of heated PM diet in piglets (Mekbungwan and Yamauchi, 2004), and of the CWVC diet in piglets (Mekbungwan et al, 2004b) and chickens (Samanya and Yamauchi, 2001). In the case of heated PM, the histological intestinal recovery was caused by a 99.15% decrease in the inhibition rate of trypsin in raw PM compared with 54.31% in heated PM (Mekbungwan and Yamauchi, 2004).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These studies suggest that the present high light microscopic parameters and the protuberated cells are much more hypertrophied in CWVC than in PM groups. In our previous studies, such histological intestinal recovery from the atrophied intestinal histology in raw PM groups was observed after feedings of heated PM diet in piglets (Mekbungwan and Yamauchi, 2004), and of the CWVC diet in piglets (Mekbungwan et al, 2004b) and chickens (Samanya and Yamauchi, 2001). In the case of heated PM, the histological intestinal recovery was caused by a 99.15% decrease in the inhibition rate of trypsin in raw PM compared with 54.31% in heated PM (Mekbungwan and Yamauchi, 2004).…”
Section: Discussionmentioning
confidence: 78%
“…Activated charcoal was reported to reduce the effects of dietary toxins by preventing intestinal absorption -E-mail: yamauchi@ag.kagawa-u.ac.jp (Anjaneyulu et al, 1993). Also, a dietary 3 g/kg powder mixture of amorphous charcoal carbon and wood vinegar compound solution (CWVC) has been shown to produce more intestinal villus hypertrophy compared with the controls, resulting in improved feed efficiency in chickens (Samanya and Yamauchi, 2001) and pigs (Mekbungwan et al, 2004b). Therefore, it was interesting to investigate the possibility that CWVC could reduce the protease inhibitory effect of dietary PM in piglet nutrition and encourage villus hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…The small intestine of these SM animals had the higher values in the intestinal villus height, cell area and cell mitosis than those of PM [19], and epithelial cells on the villus apical surface showed a dome-like shape in the duodenum [19] and in the present jejunum; epithelial cells of the PM animals were a flat shape. It has been suggested that greater villus height and numerous cell mitosis in the intestine are indicators that the function of the intestinal villi is activated [14,35], and that the dome-like cells are hypertrophied [16,17]. This literature suggests that increased light microscopic parameters and the dome-like cells in the pigs fed SM might be hypertrophied and induced by the higher crude protein content, crude protein digestibility and digestible energy of the SM than of the control.…”
Section: Discussionmentioning
confidence: 94%
“…This literature suggests that increased light microscopic parameters and the dome-like cells in the pigs fed SM might be hypertrophied and induced by the higher crude protein content, crude protein digestibility and digestible energy of the SM than of the control. Conversely, short villi were reported in pigs showing decreased body weight [16,17,37], and correspond with reductions of enzyme activities such as the mucosal lactase and sucrase [24], the lactase and alkaline phosphatase [37], and the alkaline phosphatase and disaccharidase [15]. Besides, on the apical surface of the short villi of PM groups, flattened epithelial cells were observed [16].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, the addition of wood charcoal powder including vinegar liquid improved body weight gain in chickens (Samanya and Yamauchi, 2001) and piglets (Mekbungwan et al, 2004) by activating intestinal villi and epithelial cells. This might be induced by both influences of wood charcoal and wood vinegar compound liquid.…”
Section: Discussionmentioning
confidence: 99%